BIMBINGAN DAN PELATIHAN TENTANG PENTINGNYA BAURAN PROMOSI BAGI PENGEMBANGAN USAHA DI CLOTHING & JACKET JONGGRING MALANG - Joko Samboro; Halid Hasan; Abdullah Helmi; Joni Dwi Pribadi; Rulirianto Rulirianto (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The purpose of this Community Service is to find problems faced by convection companies and at the same time provide the right solutions to achieve increased knowledge and ability of entrepreneurs in the field of operations, especially in the field of marketing management, especially the promotion mix and create opportunities for employment opportunities in community economic activities in the form of increased income the community and to develop a closer relationship between the Malang State Polytechnic and the Jonggring Business Clothing & Jacket Malang.The methode used is: observation, to observe the activities carried out by entrepreneurs in making and marketing goods, then interviews, explored to find problems and solutions to be offered and simulations, to find the most suitable alternative in order to market goods more effectively.An overview of the technology that will be applied, 1. In the form of lectures: Participants are collected in a particular room given a lecture on service material in the form of marketing management, especially the promotion mix.,2. Guidance and Training: In the form of training and organizing training specifically the promotion mix and discussion about experiences and constraints in the field.3. Simulation practice: It is a demonstration of how the entrepreneur promotes goods and with what tools the item is promoted.4. Practice displaying items on a shelf / hanger.